Installation of a gas terminal stripper and a gas/foil post stripper system at the 5.5 MV Demokritos Tandem Van de Graaff accelerator - Laoutaris, A.; Madesis, I.; Dimitriou, A.; Lagoyannis, A.; Axiotis, M.; Andrianis, M.; Benis, E. P.; Sulik, Bela; Zouros, T. J. M. (HNPS Advances in Nuclear Physics, 2019)
A gas stripper system has been installed inside the terminal of the Demokritos TANDEM accelerator, in addition to the existing foil stripper system, while two additional post strippers (one gas and one foil) were also installed in the beam line between the analyzing and switching magnets of the accelerator. These installations were necessary for the production of He-like ion beams used in the APAPES‡ project for the investigation of electron capture phenomena in ion-atom collisions using high resolution zero-degree Auger projectile electron spectroscopy in a dedicated experimental setup already in operation since two years. Older measurements have shown that for He-like ion beams foil stripping results in the production of a mixed-state beam (1s2, 1s2s 3S), while gas stripping in the terminal can produce an almost pure ground-state (1s2) beam. Thus, using both strippers, collision measurements will allow for the selective determination of state-selective capture contributions from either the metastable- (1s2s 3S) or the ground-state of the ion by judicious analysis of both associated projectile K-Auger electron spectra. In addition, post-stripping will allow us to obtain ion charge states whose production is not possible with only one stage of stripping.